2002
DOI: 10.1111/j.1752-1688.2002.tb00986.x
|View full text |Cite
|
Sign up to set email alerts
|

HYDRAULIC GEOMETRY RELATIONSHIPS FOR URBAN STREAMS THROUGHOUT THE PIEDMONT OF NORTH CAROLINA1

Abstract: Hydraulic geometry relationships, or regional curves, relate bankfull stream channel dimensions to watershed drainage area. Hydraulic geometry relationships for streams throughout North Carolina vary with hydrology, soils, and extent of development within a watershed. An urban curve that is the focus of this study shows the bankfull features of streams in urban and suburban watersheds throughout the North Carolina Piedmont. Seventeen streams were surveyed in watersheds that had greater than 10 percent impervio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
75
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 5 publications
10
75
0
Order By: Relevance
“…While both streams have similar bankfull discharges (4.7 m 3 s −1 at Chenoweth Run; 4.7 m 3 s −1 at Goose Creek) and drainage areas (14.2 km 2 at Chenoweth Run; 15.5 km 2 at Goose Creek), the level of imperviousness is quite different (33.9 percent at Chenoweth Run; 11.1 percent at Goose Creek) (Tables 1 and 2). Both Cianfrani et al [55] and Doll et al [56] found that urbanization increased bankfull channel width as compared to rural streams in the Piedmont region of the U.S. Contrary, Annable et al [57] found that urbanization did not result in significant channel enlargement for streams in Ontario, Canada.…”
Section: Bankfull Hydraulic Geometry Curvesmentioning
confidence: 97%
“…While both streams have similar bankfull discharges (4.7 m 3 s −1 at Chenoweth Run; 4.7 m 3 s −1 at Goose Creek) and drainage areas (14.2 km 2 at Chenoweth Run; 15.5 km 2 at Goose Creek), the level of imperviousness is quite different (33.9 percent at Chenoweth Run; 11.1 percent at Goose Creek) (Tables 1 and 2). Both Cianfrani et al [55] and Doll et al [56] found that urbanization increased bankfull channel width as compared to rural streams in the Piedmont region of the U.S. Contrary, Annable et al [57] found that urbanization did not result in significant channel enlargement for streams in Ontario, Canada.…”
Section: Bankfull Hydraulic Geometry Curvesmentioning
confidence: 97%
“…As little as 10% impervious cover has been linked to stream degradation, with the severity increasing as impervious cover increases [21]. Urban cover or impervious cover can result in increased peak discharges [22], channel enlargement [23,24] and associated erosion, a decline in water quality and habitat as well as a decline in macroinvertebrate community metrics [7]. Booth [6] concluded that biological condition was highly variable with low levels of anthropogenic development, but was consistently poor at high levels of impervious cover percentage and associated urban cover.…”
Section: Watershed Links To Stream Conditionmentioning
confidence: 99%
“…To recognize these impacts a "covariate" also plays an important role in this study. A covariate is a statistical term used to identify an interaction which is not measured but is observed in the record [22] [40] [41]. A covariate may be binary and is often referred to as either a hidden, lurking or dummy variable.…”
Section: Statistical Analysesmentioning
confidence: 99%